Progress in heterocyclic chemistry. - Gribble, Gordon W.; Joule, John A. (Elsevier, 2013)
Progress in Heterocyclic Chemistry is an annual review series commissioned by the International Society of Heterocyclic Chemistry (ISHC). Volumes in the series contain both highlights of the previous year's literature on heterocyclic chemistry and articles on new, developing topics of particular interest to heterocyclic chemists. The highlight chapters in Volume 25 are all written by leading researchers in their field, and these chapters constitute a systematic survey of the important original material reported in the literature of heterocyclic chemistry in 2012. As with previous volumes in the series, Volume 25 will enable academic and industrial chemists and advanced students to keep abreast of developments in heterocyclic chemistry in a convenient way. Recognized as the premiere review of heterocyclic chemistryContributions from leading researchers in the fieldSystematic survey of the important 2012 heterocyclic chemistry literature.